2014
DOI: 10.1007/s10548-014-0383-5
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and Consciousness: Study of Fronto-Parietal Gamma Synchrony in Patients with Disorders of Consciousness

Abstract: Evaluation of consciousness needs to be supported by the evidence of brain activation during external stimulation in patients with unresponsive wakefulness syndrome (UWS). Assessment of patients should include techniques that do not depend on overt motor responses and allow an objective investigation of the spontaneous patterns of brain activity. In particular, electroencephalography (EEG) coherence allows to easily measure functional relationships between pairs of neocortical regions and seems to be closely c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 51 publications
2
48
0
1
Order By: Relevance
“…Gamma connectivity has been implicated relevant in subjective consciousness (Llinas et al, 1998; Singer, 1998), and gamma coherence has been shown to be a fundamental prerequisite in the aware process and the potential to participate cognitive processes (Naro et al, 2016). In addition, gamma connectivity has been identified as an important awareness-level marker in DOC patients (Cavinato et al, 2015; Naro et al, 2016). In MCS and vegetative state (VS) patients, significant differences have been demonstrated in the responses of short-range parietal and long-range fronto-parietal gamma coherences to simple sensory stimulus modalities (Cavinato et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gamma connectivity has been implicated relevant in subjective consciousness (Llinas et al, 1998; Singer, 1998), and gamma coherence has been shown to be a fundamental prerequisite in the aware process and the potential to participate cognitive processes (Naro et al, 2016). In addition, gamma connectivity has been identified as an important awareness-level marker in DOC patients (Cavinato et al, 2015; Naro et al, 2016). In MCS and vegetative state (VS) patients, significant differences have been demonstrated in the responses of short-range parietal and long-range fronto-parietal gamma coherences to simple sensory stimulus modalities (Cavinato et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this historical context, recent studies indicate that binding of distributed information in the brain represents the basic mechanism of consciousness that manifests through neural correlates emerging in EEG specifically as fast oscillations in the γ range (40-70 Hz) (Uhlhaas et al, 2009;Lou et al, 2010;Baars et al, 2013;Cavinato et al, 2014). As might be expected, similar findings of γ oscillations were also found in the highest form of consciousness and self-awareness representing conscious recognition of one's own mental state (Jung-Beeman et al, 2004;Kounios et al, 2008;Sandkuhler and Bhattacharya, 2008).…”
Section: Introductionmentioning
confidence: 53%
“…Magnitude squared coherence was calculated at individual frequencies in 0.5 Hz intervals from 0.5 to 155 Hz between all electrode pairs in 2 s moving windows using the ‘mscohere.m’ function in the MATLAB Signal Processing Toolbox (MathWorks Inc., Natick, MA, USA). Using the approach demonstrated in previous publications from our 28,29 and other laboratories, 30,31 the coherence values were averaged over the following frequency bands: delta (δ: 0.5-4 Hz), theta (θ: 4-10 Hz), alpha (α: 10-15 Hz), beta (β: 15-25 Hz), low gamma (γ1: 25-55 Hz), medium gamma (γ2: 85-125 Hz), and high gamma (γ3: 125-155 Hz). The mean global coherence was obtained by averaging the coherence for individual channel pairs for each animal.…”
Section: Methodsmentioning
confidence: 99%